Demographic and socio‐economic factors associated with dental health among older people in NSW - Clare Ringland; Lee Taylor; Jane Bell; Kim Lim (Elsevier, 2004)
Abstract Objective: To investigate the association between oral health status and social, economic and demographic factors in community‐dwelling older people in New South Wales (NSW). Methods: Binary and multinomial logistic regression analyses were used to examine the associations between measures of oral health status (edentulous/dentate, and the frequency of toothache or mouth or denture problems in the previous 12 months) and demographic and socio‐economic factors using data from the NSW Older People's Health Survey 1999. Results: After adjusting for other factors, being edentulous was associated with being older, having no private dental insurance, being female, leaving school at less than 15 years of age, not being financially comfortable, not being a homeowner, living in a rural area, and being unable to travel alone. Among both dentate and edentulous people, increasing age and being able to travel independently were associated with decreased reporting of toothache, mouth or denture problems; while not being financially comfor table was associated with increased reporting of toothache or mouth or denture problems. The frequency of mouth or denture problems was not found to be independently associated with having private dental insurance nor with holding a health concession card. Conclusions: Among older people in NSW, oral health is associated with a range of demographic and socio‐economic factors. The results suggest that better oral health among older people is associated with a capacity to pay out‐of‐pocket dental expenses rather than with private dental insurance or having access to public‐funded dental care.